Nitric oxide synthase-like dependent NO production enhances heme oxygenase up-regulation in ultraviolet-B-irradiated soybean plants - Santa Cruz, Diego Mario (2010)
Heme oxygenase (HO) has antioxidant properties and is up-regulated by reactive oxygen species (ROS) in ultraviolet-B-irradiated soybean plants. This study shows that nitric oxide (NO) protects against oxidative damage and that nitric oxide synthase (NOS)-like activity is also required for HO-1 induction under UV-B radiation. Pre-treatments with sodium nitroprussiate (SNP), a NO-donor, prevented chlorophyll loss, H2O2 and View the MathML source accumulation, and ion leakage in UV-B-treated plants. HO activity was significantly enhanced by NO and showed a positive correlation with HO-1 transcript levels. In fact, HO-1 mRNA levels were increased 2.1-fold in 0.8 mM SNP-treated plants, whereas subsequent UV-B irradiation augmented this expression up to 3.5-fold with respect to controls. This response was not observed using ferrocyanide, a SNP inactive analog, and was effectively blocked by 2-(4-carboxyphenil)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO), a specific NO-scavenger. In addition, experiments carried out in the presence of NG-nitro-l-arginine methyl ester (l-NAME) or tungsten, well-known inhibitors of NOS and nitrate reductase, showed that NOS is the endogenous source of NO that mediates HO-1 expression. In summary, we found that NO is involved in the signaling pathway leading to HO-1 up-regulation under UV-B, and that a balance between NO and ROS is important to trigger the antioxidant response against oxidative stress.